Using IS/IT to support the delivery of Chinese medicine: a Chinese medicine clinic management system. (1st January 2014) - Lin, Catherine Han; Pittayachawan, Siddhi; Yang, Angela Wei Hong; Wickramasinghe, Nilmini
OECD countries today are focusing on ways to incorporate IS/IT to facilitate superior healthcare delivery. However, studies of IS/IT implementations for Chinese Medicine (CM) practice are very limited. We analyse western medicine (WM) and CM diagnosis and treatment processes and find that these clinical processes share some similarities. Hence, we contend that by implementing IS/IT system solutions, CM practice can also enjoy similar benefits from IS/IT as WM. This paper serves to identify a role for IS/IT in assisting CM clinic key processes as well as identify key IT investment portfolio components of such IS/IT solutions.